1866-67 N.C. Sess. Laws 103 - (:unkn) unknown (My University, 1867)
Pub. Laws, ch. 72, § 14: Property tax of one dollar on every dirk, Bowie knife, pistol, sword cane, dirk cane, and rifle cane. Violators guilty of a misdemeanor, punishable by forfeiture of the weapon.
Keywords: TAX - PROPERTY OR SALES